Mortality, morbidity, and occupational decline - Sofia Hernäs (Institute for Evaluation of Labour Market and Education Policy (IFAU), 2023)
Does the long-term economic stress of occupational decline cause health problems, or even death? This paper explores this question using Swedish administrative data, and a measure of occupational decline obtained from detailed US data on employment changes over almost 30 years. I investigate whether people who experience occupational decline have higher mortality or hospitalization rates, and in particular if they are more likely to suffer from cardio-vascular disease or deaths of despair: deaths caused by alcohol, drug or suicide. I find that workers who in 1985 worked in occupations that subsequently declined, had a 5-11 percent higher risk of death in the 30 years that followed, compared to same-aged, similar workers in non-declining occupations. For men in declining occupations, the risk of death by cardio-vascular disease was 7-14 percent elevated, while women in declining occupations faced 31-37 percent higher risk of death by despair. The risk was higher for workers who were lowest paid in their occupations
Keywords: O33; J24; I11; 330; Technological change; Occupations; Health